SINTESIS DAN KARAKTERISASI SENYAWA OKSOTRINUKLIR [Ru2Co(O)(OOCCH3)6(C5H5N)3](ClO4) - Lesbani, Aldes; Mohadi, Risfidian; Hidayati, Nurlisa (Jurnal Kimia (Journal of Chemistry), 2013)
The oxotrinuclear compound [Ru 2 Co(O)(OOCCH 3 ) 6 (C 5 H 5 N) 3 ](ClO 4 ) has been synthesized using RuCl 3 ? n H 2 O at room temperature under oxygen atmospheric condition. The oxotrinuclear complex was characterized by FT-IR spectrophotometer and mass spectrometer with cold spray ionization (CSI) method. The FT-IR spectra of the resulted oxotrinuclear compound show has specific vibration at 692 cm -1 . This absorption is related to M 3 O vibration (M= metal). CSI-mass spectra of the oxotrinuclear compound show that pyridine as ligand was fragmented in oxotrinuclear compound .
Keywords: oxotrinuclear compound, ruthenium, cobalt, FT-IR, CSI-MS